2012
DOI: 10.1055/s-0032-1310527
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Low-Dose Aspirin for the Prevention of Severe and Mild Preeclampsia: A Systematic Review and Meta-Analysis

Abstract: Low-dose aspirin initiated at or before 16 weeks reduces the risk of severe preeclampsia, but not mild preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 33 publications
0
54
0
7
Order By: Relevance
“…[4][5][6] However, after 16 weeks, aspirin prophylaxis had significantly reduced effectiveness. Developing biomarkers for the diagnosis or prediction of PE is now a priority.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, after 16 weeks, aspirin prophylaxis had significantly reduced effectiveness. Developing biomarkers for the diagnosis or prediction of PE is now a priority.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is now evidence that early (<16 weeks' gestation) intervention, through the prescription of aspirin, can reduce the prevalence of early-onset disease [22,23]. Second, first-trimester screening for aneuploidy has led to earlier attendance for antenatal care.…”
Section: Prediction and Prevention Of Petmentioning
confidence: 99%
“…Again for such small samples (five), statistical testing is inapplicable. 5. Blood count: red blood cells (RBC), white blood cells (WBC), hemoglobin (Hb) concentration, hematocrit (Ht) and platelets (Plt) 6.…”
Section: Epo As a Screening Marker For Preeclampsiamentioning
confidence: 99%
“…This involves maternal characteristics, measurements of maternal mean arterial pressure (MAP), measurements of uterine artery pulsatility index (PI) and placental growth factor (PlGF) concentration in maternal serum. Recent meta-analysis has shown that the initiation of low-dose aspirin prophylaxis at or before 16 weeks gestation may result in 50% reduction of early onset preeclampsia [5].…”
Section: Introductionmentioning
confidence: 99%